SECURITY CAPABILITY ANALYSIS OF COGNITIVE RADIO NETWORK WITH SECONDARY USER CAPABLE OF JAMMING AND SELF-POWERING - Dan, Ngoc Pham Thi; Van, Khuong Ho; Ngoc, Hanh Dang; Dac, Thiem Do; Huu, Phong Nguyen; Que, Son Vo; Ngoc, Son Pham; Pham, Lien Hong (Journal of Computer Science and Cybernetics, 2020)
This paper investigates a cognitive radio network where a secondary sender assists a primary transmitter in relaying primary information to a primary receiver and also transmits its own information to a secondary recipient. This sender is capable of jamming to protect secondary and/or primary information against an eavesdropper and self-powering by harvesting radio frequency energy of primary signals. Security capability of both secondary and primary networks are analyzed in terms of secrecy outage probability. Numerous results corroborate the proposed analysis which serves as a design guideline to quickly assess and optimize security performance. More importantly, security capability trade-off between secondary and primary networks can be totally controlled with appropriate selection of system parameters.